PENGARUH MORALITAS INDIVIDU DAN PENGENDALIAN INTERNAL TERHADAP KECENDERUNGAN TERJADINYA FRAUD (Studi Eksperimen pada Pemerintah Daerah Kabupaten Sambas) - B2091141035, U. ARI ALRIZWAN (MAKSI UNTAN, 2016)
This study aims to obtain evidence of the existence of differences in the likelihood of fraud between the level of moral reasoning (high and low) and the difference in the likelihood of fraud between the condition of the elements of internal control (existing and not existing), as well as obtain evidence of the interaction between individual morality and internal control in influencing fraud.This study uses a research design with an experimental model using two independent variables, each of which consists of two levels (2x2 factorial design). This experimental design using a factorial design analysis of variance (ANOVA), which aims to determine the main effects and interaction effects in the model of research.The results of this study show that: First, there are differences in the likelihood of fraud between individuals who have a level of high moral and individuals who have a low moral level. Second, there are differences in the likelihood of fraud between people in the condition there is an element of internal control and there are no elements of internal control. Thirdly, there is an interaction between the individual moral levels with internal control. Keywords: the individual moral, internal control, fraud.